Educational upgrading and returns to skills in Latin America: Evidence from a supply-demand framework - Pablo Acosta; Guillermo Cruces; Sebastián Galiani; Leonardo Gasparini (Latin American Economic Review, 2019)
This paper documents the evolution of wage differentials and the supply of workers by educational level for sixteen Latin American countries over the period 1991-2013. We find a pattern of rather constant rise in the relative supply of skilled and semi-skilled workers over the period. Whereas the returns to secondary education fell over time, in contrast, the returns to tertiary education display a remarkable changing pattern common to almost all economies: significant increase in the 1990s, strong fall in the 2000s, and a deceleration of that fall in the 2010s. We conclude that supply-side factors seem to have limited explanatory power relative to demand-side factors in accounting for changes in the wage gap between workers with tertiary education and the rest.
Keywords: J01; 330; Returns to skills; Latin America; Inequality; Education